Komparasi Algoritma Quicksort dan Bucket Sort pada Pengurutan Data Integer - Audy Audy (Ultimatics : Jurnal Teknik Informatika, 2015)
Data sorting is a technique that widely used as a part of a bigger process. Therefore, data sorting should not be the problem of program complexity. This paper gives the reader a comparison between two sorting algorithms, which are comparison based and non-comparison based, in time and space performance. The data type that used in this paper is an integer data type. Testing is carried out by using two types of data’s condition, which are the worst-case condition in each algorithm, and two amounts of data, which represent the maximum and minimum amount data.